CENTRE OF PRESSURE EXCURSIONS IN HEALTHY AND FUNCTIONALLY UNSTABLE PARTICIPANTS FOLLOWING A SINGLE LEG DROP JUMP LANDING; ANALYSING A SUBCONSCIOUS TIME PERIOD. Issue 7 (11th March 2014) - Gautrey, C; Watson, T; Mitchell, A
Abstract : Background: Centre of pressure (COP) excursions have been repeatedly investigated in sufferers of functional ankle instability (FAI). No study to date has analysed COP excursions in a subconscious time frame. The average fastest reaction time in young males has been identified as 200 ms, therefore anything prior to this would be beyond human conscious control. Analysis of this subconscious time period may identify deficits that are sometimes not observed when analysing a conscious time frame. Objective: To determine whether FAI participants suffer from subconscious (200 ms) and conscious (3 second) neuromuscular deficits compared to healthy controls, as measured by COP excursion. Design: Cross-sectional study. Setting: University biomechanics laboratory. Participants: A convenience sample was used to recruit twenty males with unilateral FAI and twenty male healthy controls. Inclusion criteria included males, aged 18–25 years, who were right leg dominant. Intervention: Three single leg drop jump landings from a 30 cm high bench onto a force platform. Subject group and balance analysis times were the independent variables. Main outcome measure: COP excursion in centimetres in the anterior, posterior, anteroposterior, medial, lateral and mediolateral directions, following a single leg drop jump landing. Results: When analysing the 200 ms data there was a significant (P<.0125) increase in lateral and mediolateral COP excursions in the unstable and stable ankles of the FAI group when compared to the dominant and non-dominant ankles of the healthy group. No other significant differences were identified. Conclusion: The FAI participants COP excursions were increased, but only on a subconscious level. It may be possible that after the initial 200 ms the individual is able to regain stability with conscious postural modifications. COP excursions were increased within the time frame that an ankle sprain would usually occur. Therefore, this increase may be a risk factor for repeated sprains in FAI sufferers.